Cultural sharing through visual art exhibition Dalam Bingkai by JSRB-UPSI with FSRD-ISBI - Muhamad Firdaus Ramli (Tanjong Malim, 2020)
Cultural sharing through visual art exhibition Dalam Bingkai by JSRB-UPSI with FSRD-ISBI by Muhamad Firdaus Ramli